2019
DOI: 10.3892/ol.2019.10054
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and the prognostic value of the SMYD family members in human breast carcinoma using integrative bioinformatics analysis

Abstract: Suppressor of variegation, Enhancer of Zeste, Trithorax and Myeloid-Nervy-DEAF1 domain-containing (SMYD) proteins are a set of lysine methyltransferases involved in a range of diverse biological functions, including gene expression, and regulation of skeletal and cardiac-muscle development. These proteins may additionally serve roles in a number of different types of cancer. However, the roles of the five SMYD proteins, SMYD 1/2/3/4/5, their expression patterns and prognostic value remain unclear. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…SETD3-positivity has been reported to be associated with poor prognosis in hepatocellular carcinoma (32). Similar to our expression profile, high levels of SMYD2 expression has been associated with unfavorable prognosis in different cancer types, such as breast cancer (mRNA expression) and cervical cancer (protein expression) (33,34). A recent study reported overexpression of SMYD2 in cancer vs. normal tissue, and associated higher expression of SMYD2 with enhanced proliferation in HGSC (35).…”
Section: Discussionsupporting
confidence: 86%
“…SETD3-positivity has been reported to be associated with poor prognosis in hepatocellular carcinoma (32). Similar to our expression profile, high levels of SMYD2 expression has been associated with unfavorable prognosis in different cancer types, such as breast cancer (mRNA expression) and cervical cancer (protein expression) (33,34). A recent study reported overexpression of SMYD2 in cancer vs. normal tissue, and associated higher expression of SMYD2 with enhanced proliferation in HGSC (35).…”
Section: Discussionsupporting
confidence: 86%
“…It belongs to the Smyd Family of Methyltransferases, which is recognized in diverse taxa [211]. SMYD can methylate histones and non-histone proteins and have diverse roles in chromatin remodelling as well as normal development, in cell growth and differentiation and in the regulation of a series of pathophysiological processes, including cardiac and skeletal muscle physiology and pathology and cancer [212][213][214]. As PADs cause deimination of several histones, the deimination of histone regulatory proteins, such as SMYD here, may be of considerable interest, particularly in the light of their multifaceted functions in regulating a range of histone and non-histone proteins, including histone H3 in Gallus gallus [16].…”
Section: Discussionmentioning
confidence: 99%
“…This potential prognostic mutation has not been reported previously and should be evaluated in future studies. The functional GRB2 protein acts as a negative regulator of the RAS pathway by inhibiting EGFRs [32], and SMYD4 is involved in inhibition of gene expression and has been suggested as a tumor suppressor gene [33,34]. In 4/6 patients with GRB2 alterations, alterations in SMYD4 were also present.…”
Section: Discussionmentioning
confidence: 99%